2016
DOI: 10.1038/srep31666
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 mediated genome editing in ES cells and its application for chimeric analysis in mice

Abstract: Targeted gene disrupted mice can be efficiently generated by expressing a single guide RNA (sgRNA)/CAS9 complex in the zygote. However, the limited success of complicated genome editing, such as large deletions, point mutations, and knockins, remains to be improved. Further, the mosaicism in founder generations complicates the genotypic and phenotypic analyses in these animals. Here we show that large deletions with two sgRNAs as well as dsDNA-mediated point mutations are efficient in mouse embryonic stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 37 publications
3
101
0
1
Order By: Relevance
“…There has been an intensive effort made by the community during the past 3 years to use CRISPR-based strategies for developing floxed models through zygote injections [11, 12, 17], and also through ES cell targeting strategies [20, 24, 25]. The primary objective of this work was to develop a CRISPR targeting strategy suitable for both high- and low-throughput generation of floxed animal models.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an intensive effort made by the community during the past 3 years to use CRISPR-based strategies for developing floxed models through zygote injections [11, 12, 17], and also through ES cell targeting strategies [20, 24, 25]. The primary objective of this work was to develop a CRISPR targeting strategy suitable for both high- and low-throughput generation of floxed animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The spermatozoa of patients with DNAJB13 mutations were similar to the findings in chimeric mice (Oji et al ., ) but not the tailless and short‐tailed phenotype. Guan J suggested that the silencing of RSP16 in Chlamydomonas reinhardtii did not massively alter the structure of the RSs or the axoneme but delayed the initiation and propagation of flagellar bending (Toure et al ., ), which could explain why patients with mutations have sperm flagellar motility and display structure disordered and twitching in sperm flagellar and low sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Oji et al . generated chimeric mice with biallelic mutant embryonic stem cells (ESCs) for the Dnajb13 gene; they found suppression of the phenotype of hydrocephalus and sperm malformation (Oji et al ., ). These findings suggest that this protein may participate in the motility of mature mouse spermatozoa.…”
Section: Introductionmentioning
confidence: 97%
“…Embryonic stem (ES) cells (EGR‐101) (Fujihara, Kaseda, Inoue, Ikawa, & Okabe, ) were transfected with linearized 3xFLAG‐dCas9‐IG/pSKII‐ROSA, as described previously (Oji et al., ). ES cells retaining the transgene in the Rosa26 locus were injected into blastocysts (ICR × ICR) to generate chimeric mice.…”
Section: Methodsmentioning
confidence: 99%